Gout, Hyperuricaemia and Crystal-Associated Disease Network (G-CAN) common language definition of gout. Issue 2 (26th April 2021) - Murdoch, Rachel; Barry, Michael J; Choi, Hyon K; Hernandez, Daniel; Johnsen, Brianne; Labrador, Manuel; Reid, Susan; Singh, Jasvinder A; Terkeltaub, Robert; Vázquez Mellado, Janitzia; Dalbeth, Nicola
Abstract : Objective: To develop a Gout, Hyperuricaemia and Crystal-Associated Disease Network (G-CAN) common language definition of gout, with the goal of increasing public understanding and awareness, and ensure consistent and understandable messages about gout. Methods: A G-CAN working group that included patients, physicians and nongovernmental organisation (NGO) representatives was formed to develop a common language definition of gout for use with the public, media, healthcare providers and stakeholders. A literature search and interviews with patients, healthcare workers and stakeholders informed development of the definition. Following consultation with G-CAN members and partners, the definition was endorsed by the G-CAN board. Results: The G-CAN common language definition of gout describes the epidemiology, pathophysiology, symptoms and impact, risk factors, comorbidities, management and healthcare and workforce considerations. Detailed information is provided to support the content of the definition. After the publication of the English-language version, the definition will be available for translation into other languages by G-CAN members. Conclusion: G-CAN has developed a concise and easily understandable statement describing gout in language that can be used in conversations with the lay public, media, NGOs, funders, healthcare providers and other stakeholders.